The Effect of Inhalation Aromatherapy on Decrease Anxiety Levels of Patients with Chronic Renal Failure Undergoing Hemodialysis in Wangaya District Hospital - Komang Ayu Surya Dewi (Coping: Community of Publishing in Nursing, 2013)
Chronic renal failure patients who choose hemodialysis as renal function replacement therapy will undergo lifelong treatment unless patient is undergoing a kidney transplant. Dependence of the hemodialysis patient's lifetime can have broad impact and cause physical, psychosocial, and economic problems. Given the complexity of the problems that arose had caused anxiety in these patients. Anxiety of patients with chronic renal failure undergoing hemodialysis can be treated with inhalation aromatherapy. Patient inhaled aromatherapy time of the stabbing until hemodialysis lasted for 30 minutes. This study aims to determine the effect of inhalation aromatherapy on reducing anxiety levels of patients with chronic renal failure undergoing hemodialysis. This study is a pre-experimental studies (one group pre-test and post-test design). Samples consisted of 30 people elected purposive sampling. The data was collected using a structured interview questionnaire Beck Anxiety Inventory. The results of 30 respondents that anxiety levels decreased after inhalation of aromatherapy administered. Based on data analysis using the Wilcoxon Sign Rank Test results are statistically significant with a significance level of p = 0,000 (p ? 0,05) means that there is the effect of giving an inhalation aromatherapy to decrease anxiety levels of patients with chronic renal failure undergoing hemodialysis.